Posteriorly displaced salter halter fracture-dislocation at the sternoclavicular joint with associated thoracic outlet syndrome: A case report. (2020) - McAleese, Timothy; Curtin, Mark; Collins, Denis
Highlights: Posterior sternoclavicular joint fracture-dislocations are a rare and often-missed injury in trauma. Posterior displacement at the SCJ is a true emergency and can be associated with compression of vital structures and thoracic outlet syndrome. Closed or open reduction of these injuries is generally advised but is associated with considerable risk. Conservative management can be successful in the presence of physeal injury but has never been described in the setting of thoracic outlet syndrome. Abstract: Introduction: Posterior sternoclavicular joint fracture-dislocations are a rare and often missed diagnosis. They represent <1% of shoulder girdle injuries and are nine times less common than anterior dislocations. These injuries can be associated with life-threatening complications such as compression of the superior mediastinal structures including the great vessels and brachial plexus. Presentation of Case: This case describes a 23-year-old woman who was initially discharged from the emergency department but represented 8 days later with symptoms of venous and neurogenic thoracic outlet syndrome as a result of posterior displacement of a Salter 2 fracture-dislocation at the sternoclavicular joint. Multidisciplinary consensus and patient preference resulted in the conservative management of her injuries with intensive rehabilitation and close outpatient follow-up. Discussion: The evidence regarding this rare injury is evolving. It currently suggests all posteriorly displaced fracture-dislocations at the sternoclavicular joint are reduced. Closed reduction is often unsuccessful and open reduction is high risk and must be undertaken in the presence of a cardiothoracic surgeon which may not always be appropriate or in line with patient preferences. There are limited reports of successful conservative management of these injuries and none in the setting of thoracic outlet syndrome. Conclusion: This unique case report is the first to describe outcomes of a conservatively managed, posteriorly displaced fracture-dislocation at the sternoclavicular joint with associated venous and neurogenic thoracic outlet syndrome. This information will benefit select patients.